The Speech of Online Taxibike Directive in Demak Regency - Himawan, Adi; Rustono, Rustono; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Transportation is a service to help facilitate the activities. One of the means of transportation that can be used as a research object is a taxibike online. This study aims to find the types, functions, and factors of directive speech on taxibike online in Demak Regency. Data collection techniques are listening to techniques with tapping techniques, followed by conversational engagement listening techniques, recording techniques, and note-taking techniques. Types of directive speech found direct directive utterances include direct declarative speech, interrogative mode direct speech, and imperative mode direct speech, indirect directive speech includes indirect directive utterance declarative mode, indirect directive utterances interrogative mode, and indirect directive utterances imperative mode, speech literal directive includes literal direct directive speech and literal indirect directive speech, indirect directive speech includes indirect directive speech and indirect directive speech. Speech functions include the functions of requiring, asking, ordering, prohibiting, giving permission, and suggesting. The speech factors were analyzed and described according to Hymes' theory including setting and scene, participant, ends, act sequence, key, norm, and genre. The dominance of the type of directive utterance that is most found is direct directive utterance with interrogative mode. The dominant function that is often found is the directive utterance of the question function. The dominance of the directive speech factor is the speaker participant factor.